Persepsi Pejabat Pengguna Anggaran terhadap Efektivitas Implementasi Anggaran Berbasis Kinerja Ditinjau dari Aspek Rasional (Survei pada Pemerintah Kota Surakarta) - Djoko Suhardjanto; Bayu Tri Cahyo (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
The objectives of this research is to examine the influence of rational aspects such as resources, information, goal orientation and the measuring performance upon the implementation of the effectiveness performance based budgeting. Tthis research uses purposive sampling to get data. There are 72 respondents who have responsibilities in the budgeting in district working unit in local government Surakarta. Results of multiple regression analysis show that resources variable (p-value 0.031) and performance measurement system (p-value 0.005) affect positively the effectiveness of the implementing performance based budgeting in local government. It means that an increase in resources and development in performance measurement will increase the effectiveness of budgeting.Keywords: effectiveness, performance, budgeting, resources, information, measurement